The prevalence role of monocyte chemoattractant protein-1 in hashimoto's thyroiditis via various stimuli mechanisms - Israa Burhan Raoof; Raghad Abdulmahdi Mohsin; Zahraa Ahmed Okhti (Wolters Kluwer Medknow Publications, 2021)
Hashimoto's thyroiditis (HT) is an autoimmune disease occurred at any age especially in the 30 and 50 years of patient, with time thyroid gland is lost its function, as the lymphocytes produce inflammatory cytokines, have a direct effect on the thyroid gland function. The monocyte chemoattractant protein (MCP) produced by the podocyte and monocyte in response to these stimuli and has a role in the feedback based on thyroid hormones therefore MCP is increased secretion depending on thyroid hormones; also it's increased with enlargement of adipocyte tissue, i.e., in patients with high body mass index (BMI), there is a relationship between Hashimoto's disease and obesity, that has an effect on the thyroid gland function. Obesity have important role on thyrostimulated hormones (TSHs), as it has a great effect on metabolism and expansion of the thyroid gland; researchers have previously found that obese individuals have higher serum TSH levels. The results of the study have reported that MCP 1, TSH, and BMI levels were highly significant increased in sera of G2 compared with G1, while T3 and T4 levels were highly significant decreased in sera of G2 compared with G1 in referring to G1: Healthy control group while G2: HT patients.